Influence of exogenous application of melatonin on biochemical changes of avocado fruit during ripening - Cam Tu, Vu Thi; Thanh Tra, Huynh Thi; Duc An, Hoang; Duy Thanh, Le; Hoang, Thi Minh Nguyet; Thi Hue, Truong (Academia Journal of Biology, 2022)
Melatonin (MT) is considered as a plant growth regulator, has extensive functions and plays a prominent role in ripening and fruit senescence. However, there has been no report regarding the influence of melatonin on biochemical changes of avocado fruit (Persea americana Mill.) during ripening. In this study, the cultivar of avocado fruit “034” was treated with MT at 0.1 mM and 0.5 mM to evaluate biochemical changes relating to the fruit quality during storage at 22 oC ± 1 and 75–80% relative humidity. The results showed that postharvest fruits treated with MT effectively delayed the changes in ripening parameters and that the effectiveness depends on MT concentration. Application of MT (0.5 mM, immersion for 2 hours) to “034” avocado enhanced total phenol and flavonoid accumulation and maintained titratable acidity, total soluble solids, lipid and ascorbic acid contents. Furthermore, 0.5 mM MT treatment effectively suppressed the increase of total sugar and reduced weight loss compared with the control fruit after 12 days of storage. The results indicate that the MT application could be a useful tool to maintain avocado fruit quality during the postharvest stage.